Sweden, the first country to achieve the Joint United Nations Programme on HIV/AIDS (UNAIDS)/World Health Organization (WHO) 90‐90‐90 continuum of HIV care targets - Gisslén, M (HIV Med, 2016)
OBJECTIVES: The Joint United Nations Programme on HIV/AIDS (UNAIDS)/World Health Organization (WHO) 90‐90‐90 goals propose that 90% of all people living with HIV should know their HIV status, 90% of those diagnosed should receive antiretroviral therapy (ART), and 90% of those should have durable viral suppression. We have estimated the continuum of HIV care for the entire HIV‐1‐infected population in Sweden. METHODS: The Swedish InfCare HIV Cohort Study collects viral loads, CD4 counts, and viral sequences, along with demographic and clinical data, through an electronic clinical decision support system. Almost 100% of those diagnosed with HIV infection are included in the database, corresponding to 6946 diagnosed subjects living with HIV‐1 in Sweden by 31 December 2015. RESULTS: Using HIV surveillance data reported to the Public Health Agency of Sweden, it was estimated that 10% of all HIV‐infected subjects in Sweden remain undiagnosed. Among all diagnosed patients, 99.8% were linked to care and 97.1% of those remained in care. On 31 December 2015, 6605 of 6946 patients (95.1%) were on ART. A total of 6395 had been on treatment for at least 6 months and 6053 of those (94.7%) had a viral load < 50 HIV‐1 RNA copies/mL. CONCLUSIONS: The 2014 UNAIDS/WHO 90‐90‐90 goals for HIV care means that > 73% of all patients living with HIV should be virologically suppressed by 2020. Sweden has already achieved this target, with 78% suppression, and is the first country reported to meet all the UNAIDS/WHO 90‐90‐90 goals.